2020
DOI: 10.3390/jcm9092765
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adding Transcutaneous Spinal Cord Stimulation (tSCS) to Sit-To-Stand Training in People with Spinal Cord Injury: A Pilot Study

Abstract: Spinal cord stimulation may enable recovery of volitional motor control in people with chronic Spinal Cord Injury (SCI). In this study we explored the effects of adding SCS, applied transcutaneously (tSCS) at vertebral levels T10/11, to a sit-to-stand training intervention in people with motor complete and incomplete SCI. Nine people with chronic SCI (six motor complete; three motor incomplete) participated in an 8-week intervention, incorporating three training sessions per week. Participants received either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 60 publications
0
48
0
Order By: Relevance
“…Given that tSCS has typically been applied continuously at 15-30 Hz, either in traditional biphasic waveforms ( Hofstoetter et al, 2013 , 2015 ; Al’joboori et al, 2020 ) or in HF (10kHz) bursts ( Gerasimenko et al, 2015c ; Gad et al, 2017 ; Sayenko et al, 2019 ), we compared their immediate effects on corticospinal excitability. HF waveforms minimize the discomfort of traditional waveforms applied transcutaneously at similar currents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that tSCS has typically been applied continuously at 15-30 Hz, either in traditional biphasic waveforms ( Hofstoetter et al, 2013 , 2015 ; Al’joboori et al, 2020 ) or in HF (10kHz) bursts ( Gerasimenko et al, 2015c ; Gad et al, 2017 ; Sayenko et al, 2019 ), we compared their immediate effects on corticospinal excitability. HF waveforms minimize the discomfort of traditional waveforms applied transcutaneously at similar currents.…”
Section: Discussionmentioning
confidence: 99%
“…Since any changes in excitability could potentially contribute to the immediate improvements in motor function, we adopted a condition-test approach, whereby we assessed the short-term (<1 s) effects of tSCS or PNS stimuli on corticospinal excitability, by delivering TMS shortly after the stimuli. tSCS, when used therapeutically in people living with SCI, is typically delivered at between 15 and 30 Hz ( Hofstoetter et al, 2013 , 2015 ; Al’joboori et al, 2020 ) or in ultra-high frequency (HF) bursts (10 kHz bursts delivered at 15-30 Hz), which are thought to minimize the pain and discomfort of tSCS delivered with traditional waveforms ( Gerasimenko et al, 2015a , b ; Gad et al, 2017 ; Sayenko et al, 2019 ). Therefore, we examined the immediate effects of brief 30Hz trains of stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…When applied over the lumbar spinal cord, neurophysiological and computer modelling studies have complementarily suggested the activation of large- to medium-diameter afferent fibers within the posterior roots, which are also the principal neural targets of lumbar eSCS for motor effects [ 6 , 7 , 9 , 10 , 11 , 12 ]. Independent studies have pointed at the potential of tSCS to augment residual voluntary motor function [ 13 , 14 , 15 , 16 ] and to decrease lower-extremity spasticity in SCI [ 17 , 18 , 19 ]. Importantly, the effects on spasticity were shown to last for several hours beyond the application [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electrode configurations with regard to position and location varied substantially across experiments (Tables 6 and 7 ). The cathode was positioned dorsally over the vertebral column in the majority of studies, otherwise electrodes were used that alternated polarity within a biphasic pulse [ 16 18 , 23 , 40 , 69 , 70 ]. Some studies specified a paravertebral dorsal electrode orientation [ 16 19 , 68 ], whereas most others placed the electrode in the midline over the vertebral column [ 14 , 20 , 23 , 25 , 26 , 36 , 37 , 40 44 , 67 , 69 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cathode was positioned dorsally over the vertebral column in the majority of studies, otherwise electrodes were used that alternated polarity within a biphasic pulse [ 16 18 , 23 , 40 , 69 , 70 ]. Some studies specified a paravertebral dorsal electrode orientation [ 16 19 , 68 ], whereas most others placed the electrode in the midline over the vertebral column [ 14 , 20 , 23 , 25 , 26 , 36 , 37 , 40 44 , 67 , 69 72 ]. Many studies targeted a single site, however, 8 out of 14 therapeutic investigations favoured the stimulation of multiple sites simultaneously [ 36 , 37 , 40 43 , 67 , 71 ].…”
Section: Resultsmentioning
confidence: 99%